(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this paper we have defined and proved that the????????∗????-closure is a Kuratowski closure operator on the ideal topological space (X, τ, ????). Also, we have introduced ????????∗????- kernel,????????∗????-derived set, ????????∗????-Border, ????????∗????-Frontier and ????????∗????-Exterior. Its characterization and properties investigated and exploredin ideal topological space.